Personality Types and their Relationship with Depression among teachers in local schools in Amman - Khawaldeh, Omar Abdallah (Journal of Educational and Psychological Sciences, 2021)
The Study amid to Reveal the Personality Types and their Relationship with Depression among teachers in local schools in Amman. The descriptive and analytical approach was used through a sample of (135) male and female teachers in public schools in Amman. The Eysenck personality scale and the Beck scale for depression were used. Depression and there are no statistically significant differences at the level of significance (α = 0.05) between personality types and depression among teachers due to gender. Statistically significant differences at the significance level (α = 0.05) between personality styles and depression among teachers due to job experience. The study recommended the necessity of giving a prominent role to social, cultural, media and educational institutions that can carry out an educational aspect to reduce unacceptable behavior patterns.